+0  
 
0
96
1
avatar

Solve (2x - 3)/6 - (4 - x)/36 = (x + 2)/9.

 Jun 7, 2020
 #1
avatar+9998 
+1

Solve (2x - 3)/6 - (4 - x)/36 = (x + 2)/9.

 

Hello Guest!

 

 \(\large \frac{2x-3}{6}-\frac{4-x}{36}=\frac{x+2}{9}\\\)

 \(\large \frac{(2x-3)6}{6\cdot 6}-\frac{4-x}{36}=\frac{(x+2)4}{9\cdot4}\\\)    | form common denominator

 \(\large \frac{12x-18}{36}-\frac{4-x}{36}=\frac{4x+8}{36}\\\)        | \(\times 36\)

 \(12x-18-(4-x)=4x+8\)  | remove the bracket

 \(12x-18-4+x=4x+8\)     | separate variables and constants

 \(12x+x-4x=8+18+4\)     | add

  \(9x=30\)                                       | divide by 9

  \(x=\frac{30}{9}=\frac{10}{3}=3\frac{1}{3}=3.\overline {33}\)

laugh  !

 Jun 7, 2020
edited by asinus  Jun 7, 2020

38 Online Users

avatar